Sistem Informasi Pengelolaan Iuran Rukun Kematian Berbasis Web Pada Yayasan Bunga Cempaka Bogor Dengan Menggunakan Metode Prototype - Hadidl Wiranda Ramadhan; Sofyan Mufti Prasetiyo (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The Bunga Cempaka Bogor Foundation is a foundation located in the Bojong Gede Village, Tajur Halang District, Bogor, which manages death contributions for residents of the Pura Arista Cluster. The fee is a mandatory monthly contribution paid by residents (per household) on the basis of a mutual agreement. This contribution aims to ease the burden on family members who are affected by the burden of death. In the management of death contributions, contributions are often uneven and data recording is not organized, resulting in difficulty finding data that has been previously inputted. So a web-based system was created as a tool in data processing and to support accountability in presenting effective and efficient reports and making it easier to produce quality information as needed. In developing this system, researchers used the Prototype methodology as a system development method. With this system, the process of managing death contributions between the foundation and the pillars of death becomes more well-organized and can improve the quality of service and effectiveness of the foundation's performance.